Magnetometer Design for Measuring Ultralow DC Magnetic Fields Using YBa2Cu3O7-x Superconductors - (:unkn) unknown (SPRINGER, 2013)
In the present work we examined a special sensor design using a YBa2Cu3O7-x superconductor as a sensing element for the detection of ultralow DC magnetic fields. The experimental results have shown that the sensor signal, which is the second harmonic signal generated by co-application of AC and DC fields to high-T (c) superconductors, varies linearly with the applied DC field even in the -0.5 Oe to 0.5 Oe range. The critical factors affecting the strength of the second harmonic signal, such as the frequency and amplitude of the AC field, the intergrain critical field H (c1J) , and the minimum field required for penetration through the entire specimen H (au), were optimized. In this way we could detect DC magnetic fields as low as 1 nT.
Keywords: 2nd harmonic signal; High-T-c superconductor; DC-magnetometer; Ultra-low DC field measurements; Magnetic field sensor